Water Quality - Sarkkola, Sakari; Nieminen, Mika; Laudon, Hjalmar; Clarke, Nicholas; Hasselquist, Eliza Maher (Springer Nature Switzerland, 2025)
Conventional forest operations can exert significant impacts on the hydrology and water quality of downstream aquatic environments. Few research results have been published on the impacts of continuous cover forestry (CCF) on water quality. CCF could be useful for reducing nutrient, carbon, and suspended solid exports in waterways. CCF may be a better alternative to rotation forestry (RF) on mineral soils and drained peatlands. Further research is needed on the many processes controlling nutrient and carbon exports in CCF and RF.
Keywords: upland soil; peatland; water loading; brownification; forest hydrology